Factors influencing COVID-19 testing: a qualitative study in Bhutan - Sonam Yangchen; Solip Ha; Abraham Assan; Tashi Tobgay (BMC, 2022)
Abstract Background The COVID-19 pandemic has reaffirmed an all-knowing truth-that health is central in the 2030 Sustainable Development Agenda. To fully control the infection in a community, accurate testing of suspected cases along with effective tracing and appropriate treatment (3Ts) is still crucial to slowing transmission of COVID-19 virus This study explored factors that influenced COVID-19 testing in Bhutan. The lessons learned from this study could serve as a roadmap to strengthen the current respond to COVID-19 and for future outbreaks, particularly in low- and middle-income countries. Methods The study employed an exploratory qualitative design. Data collection methods included interviews with key informants with a purposively selected sample of 20 participants. The interview findings were augmented by reviewing both published literature and unpublished documents.For the analysis of qualitative interviews, a hybrid approach of inductive and deductive coding and theme development was conducted to analyze findings. A tailored version of the WHO Health System Framework incorporating the Essential Public Health Function was used to guide data interpretation. Results Political will through the influence and leadership of the King of Bhutan played a crucial role in raising attention to the problem, and provision of adequate financial and technical relief to ensure that all people irrespective of their socioeconomic status do not pay to get tested of COVID-19. A compassionate leadership, Whole of Society approach is backed by the scientific community, functional health systems and community-based approaches, use of information technology for awareness creation and improved surveillance system, and fast-tracked COVID-19 testing service delivery. Conclusion Bhutan's success relied greatly on multi-sectoral and systematic approach during policy design, implementation and monitoring, and active collaborative efforts involving consultation and engagements with a broad range of local (community members), national and global actors for accelerated COVID-19 testing. These efforts were made possible through improved health governance and leadership at all levels of the society.